74.7k views
19 votes
5x - 4y = -10
y = 2x - 5
2 =
y =

5x - 4y = -10 y = 2x - 5 2 = y =-example-1
User Ctrlbrk
by
5.0k points

1 Answer

8 votes

Answer:

x=10

y=15

Explanation:

Since we know y in terms of x, we can use substitution and say instead of-

5x-4y=-10

5x-4(2x-5)=-10

5x-8x+20=-10

-3x=-30

x=10

Substitute x into the equation-

y=2x-5

y=2(10)-5

y=20-5=15.

User Vishal Shukla
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.